2019
DOI: 10.1016/j.nbd.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound and apoptotic death in the neonatal primate brain

Abstract: Apoptosis is triggered in the developing mammalian brain by sedative, anesthetic or antiepileptic drugs during late gestation and early life. Whether human children are vulnerable to this toxicity mechanism remains unknown, as there are no imaging techniques to capture it. Apoptosis is characterized by distinct structural features, which affect the way damaged tissue scatters ultrasound compared to healthy tissue. We evaluated whether apoptosis, triggered by the anesthetic sevoflurane in the brains of neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
(132 reference statements)
0
12
0
Order By: Relevance
“…Twelve (12/23) studies reported that all animals survived the anesthetic procedure 24,26–29,33,34,37–40,42 . Other 11/23 studies did not address animal survival following exposure 16,22,23,25,30–32,35,36,41,43 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve (12/23) studies reported that all animals survived the anesthetic procedure 24,26–29,33,34,37–40,42 . Other 11/23 studies did not address animal survival following exposure 16,22,23,25,30–32,35,36,41,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Eighty percent (12/15) of mechanically ventilated studies monitored fraction of inspired oxygen 16,23,26–29,33,35,37–40 . Eighty‐seven percent (20/23) of studies monitored blood pressure, 16,23–30,32–41,43 and ninety‐one percent (21/23) of studies monitored temperature 16,23–30,32–43 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations